Երևանի բնակչության կողմից բրնձի սպառման արդյունքում աֆլատոքսին B1միկոտոքսինի ներգործության գնահատում - Պիպոյան,Դ. Ա.; Պողոսյան, Է. Վ.; Ստեփանյան, Ս. Ա.; Բեգլարյան, Մ. Ռ. (ՀԱԱՀ հիմնադրամ)
Հետազոտությունն իրականացվել է Երևանի բնակչության կողմից բրնձի սպառման արդյունքում աֆլատոքսին B1 միկոտոքսինի ներգործությամբ պայմանավորված հնարավոր առողջական ռիսկերը գնահատելու նպատակով: Ռիսկի գնահատումը կատարվել է ներգործության սահմանի (MOE) հաշվարկման մեթոդով՝ ըստ աֆլատոքսին B1-ի համար հաստատված առողջապահական ուղեցուցային արժեքի: Ստացված արդյունքների (MOE<10000) համաձայն՝ բրնձի նմուշներում աֆլատոքսին B1-ի միջին պարունակությամբ պայմանավորված ներգործությունը հանրային առողջապահական խնդիր է: Исследование проведено с целью оценки возможных рисков для здоровья, вызванных воздействием микотоксина афлатоксина В1 в результате потребления риса населением г. Еревана. Оценка рисков проводилась методом определения предела действия (MOE) с учетом установленного нормативного значения афлатоксина В1. Согласно полученным результатам (MOE<10000), воздействие средних уровней афлатоксина В1, обнаруженных в образцах риса, является проблемой общественного здравоохранения. Aflatoxin contamination in cereals poses a significant food safety and public health issue worldwide. Cereals, including rice, are a staple food in the diet of the Armenian population. This study aimed to assess the potential health risks associated with the exposure to aflatoxin B1 mycotoxin through rice consumption among the population of Yerevan. The daily intake of aflatoxin B1 through the rice consumption was estimated for the adult population across all administrative regions. The margin of exposure (MOE) method was used to evaluate the health risks associated with aflatoxin B1 exposure, with values less than 10000 considered a public health concern. The results indicated that the MOE for aflatoxin B1 exposure through rice consumption among the Yerevan population was less than 10000, which indicates the public health concern. Even the amounts of aflatoxin B1 within permissible levels were found to be potentially risky for the health of the population. Moreover, the MOE method used in this study can be a useful tool for assessing the risks associated with other food contaminants and guiding the development of appropriate risk management strategies. Hence, this study emphasizes the need for ongoing monitoring of aflatoxin levels in cereals, to ensure the safety of the food supply and protect public health.
Keywords: Սննդագիտություն և տեխնոլոգիա